Regional outcomes of severe acute respiratory syndrome coronavirus 2 infection in hospitalised patients with haematological malignancy. (13th July 2020) - Booth, Stephen; Willan, John; Wong, Henna; Khan, Dalia; Farnell, Rachel; Hunter, Alicia; Eyre, Toby; Katz, Harley; Dungarwalla, Moez; Chen, Lucia; Browning, Joe; Polzella, Paolo; et al.
Abstract: Objectives: We sought to characterise the outcomes of patients with haematological malignancy and severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection in hospital in our regional network of 7 hospitals. Methods: Consecutive hospitalised patients with haematological malignancy and SARS‐CoV‐2 infection were identified from 01/03/2020 to 06/05/2020. Outcomes were categorised as death, resolved or ongoing. The primary outcome was preliminary case fatality rate (pCFR), defined as the number of cases resulting in death as a proportion of all diagnosed cases. Analysis was primarily descriptive. Results: 66 Patients were included, overall pCFR was 51.5%. Patients ≥ 70 years accounted for the majority of hospitalised cases (42, 63%) and fatalities (25, 74%). Mortality was similar between females (52%) and males (51%). Immunosuppressive or cytotoxic treatment within 3 months of the diagnosis of SARS‐CoV‐2 infection was associated with a significantly higher pCFR of 70%, compared with 28% in those not on active treatment ( P = .0013, 2 proportions z test). Conclusions: Mortality rates in patients with haematological malignancy and SARS‐CoV‐2 infection in hospital are high supporting measures to minimise the risk of infection in this population.